2019
DOI: 10.1186/s12876-019-1105-y
|View full text |Cite
|
Sign up to set email alerts
|

Stress ulcer prophylaxis with proton pump inhibitors or histamine 2 receptor antagonists in critically ill adults - a meta-analysis of randomized controlled trials with trial sequential analysis

Abstract: BackgroundProton pump inhibitors (PPI) and histamine 2 receptor antagonists (H2RA) have been widely used as stress ulcer prophylaxis (SUP) in critically ill patients, however, its efficacy and safety remain unclear. This study aimed to assess the effect of SUP on clinical outcomes in critically ill adults.MethodsLiterature search was conducted in PubMed, EMBASE, Web of Science, and the Cochrane database of clinical trials for randomized controlled trials (RCTs) that investigated SUP, with PPI or H2RA, versus p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 54 publications
0
10
0
2
Order By: Relevance
“…A meta-analysis also found that PPIs are more effective than H2RAs, but may also increase the risk of VAP ( Alquraini et al, 2017 ). Zhou et al believed that for high-risk critically ill patients, PPIs and H2RAs can significantly reduce gastrointestinal bleeding, with both potentially increasing the pneumonia incidence ( Zhou et al, 2019 ). Other studies had shown that there was no difference in the effect of PPI on VAP compared with H2RAs, but PPI had a better anti-gastrointestinal bleeding effect ( Arriola et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A meta-analysis also found that PPIs are more effective than H2RAs, but may also increase the risk of VAP ( Alquraini et al, 2017 ). Zhou et al believed that for high-risk critically ill patients, PPIs and H2RAs can significantly reduce gastrointestinal bleeding, with both potentially increasing the pneumonia incidence ( Zhou et al, 2019 ). Other studies had shown that there was no difference in the effect of PPI on VAP compared with H2RAs, but PPI had a better anti-gastrointestinal bleeding effect ( Arriola et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…Patients with IMV are often associated with stress ulcer risk, and preventive application of gastric acid secretion inhibitors (GASIs) can significantly reduce gastrointestinal bleeding ( Zhou et al, 2019 ). The most commonly used drugs are proton pump inhibitors (PPIs) and histamine 2 receptor antagonists (H2RAs).…”
Section: Introductionmentioning
confidence: 99%
“…Recent improvements in the quality of management for these patients have decreased the incidence of upper gastrointestinal bleeding to 2‐5%. 980 However, preventing stress ulcers is important because the onset of upper gastrointestinal bleeding was correlated with an increased mortality rate. 981 Preventative methods include the administration of anti‐ulcer drugs such as acid‐suppressive medications, antacids, and mucosa protective anti‐gastric ulcer drugs.…”
Section: Methods Used For Creating This Guidelinementioning
confidence: 99%
“…Upper gastrointestinal bleeding associated with stress ulcers is a problem among critically ill patients such as those with sepsis. Recent improvements in the quality of management for these patients have decreased the incidence of upper gastrointestinal bleeding to 2–5% [ 1018 ]. However, preventing stress ulcers is important because the onset of upper gastrointestinal bleeding was correlated with an increased mortality rate [ 1019 ].…”
Section: Methods Used For Creating This Guidelinementioning
confidence: 99%